The Meaning of Money as a Determinant of Voting Behavior in Jember: A Phenomenology Study - Haressa Lintang Rizkika; Iffan Gallant EL Muhammady (SS&H: Studies in Social Sciences and Humanities, 2024)
In today's Indonesia, organizing a democratic party's general election (election) is commonly referred to as "money politics." A democratic party's political decision should ideally be based on a shared interest in the candidate's vision and goal, or on shared ideology, and carried out in accordance with societal values and conventions. However, money politics has become a common tactic in our elections as a means of gaining voters. This study attempts to discuss this phenomenon through a qualitative approach and a phenomenology study, with the results being a description of the meaning of money and the psychological reasoning behind vote-buying behavior on both sides. The findings show that 'giving', in the informant's opinion, is an alms, affection, and present that should be valued rather than a violation of the law or a negative thing. Second, giving is perceived as something that does not contradict one's or society's values and norms. The pattern of interactions between political candidates and voters in a vertical relationship develops a strong need relationship because the modeling process that results from this practice is done by many people and has been done for years. Third, voters have the resources and opportunities to engage in money politics or vote-buying activities. Where resources support the practice of money politics' long-term viability due to lax law enforcement and private-sector activities.